National Electronic Injury Surveillance System sports-related arm fractures in the USA: thrower`s fractures - Yu, A.; Janney, C. F.; Panchbhavi, V. K.; Jupiter, D. C. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: Humerus fractures are common in the USA. The purpose of this study was to utilize the National Electronic Injury Surveillance System: 1) to compare overall and age stratified incidence rates of proximal and distal arm fractures presenting to USA emergency departments; 2) to compare relative humerus fracture locations by age; and 3) to compare anatomical humerus fracture locations stratified by sports between 2005-2009 and 2015-2019. METHODS: The National Electronic Injury Surveillance System was used to obtain estimated proximal and distal arm fractures between 2005-2009 and 2015-2019. Fracture rates were normalized using USA census estimates and stratified by age. Case summaries were filtered for anatomical and non-specific (proximal, middle, distal third) humerus fractures. Relative humerus fractures, inclusive of anatomical and non-specific fractures, were stratified by age and compared between 2005-2009 and 2015-2019. Anatomical fractures were stratified by sports. ?2 tests were used to compare fracture rates between time periods. RESULTS: There was a decrease (P<0.0001) in proximal and distal arm fracture rates and a difference (P<0.0001) in fracture rates with respect to age between 2005-2009 and 2015-2019. There was a significant difference in reported relative humeral fractures (P<0.0001) between the two periods. Impact related sports trauma accounted for most fracture cases for both periods. Non-impact related sports trauma consisted entirely of thrower`s fractures. CONCLUSIONS: USA proximal and distal arm fracture rates decreased, and distributions differed by age between 2005-2009 and 2015-2019. Relative humerus fractures differed by time periods. One major non-impact sports related humerus fracture was extreme external rotational torque from throwing.